THE MOTIVE OF PENITENCE/SALVATION IN THE STORY OF «BLACKTHORN IN THE LEG» BY IVAN FRANKO - Вівчарик, Н. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article analyzes the genre, plot and compositional features of «Blackthorn in the Leg», the story by Ivan Franko. It is proved that the title of the story serves as a primary ideological and semantic signal activating both the religious and the folklore context. There is a clear illustration of using parabola principle in the story, which allowed the author to combine two events, which had been too distant one from another in time, and «to read» them through the prism of the motive of penitence/salvation. The image of thorn symbolizes the inevitable trials, which are to be overcome by any human being on the way of learning existential truths. By the flash fiction, Ivan Franko managed to retell the whole story of the hero’s «rebirth» and to motivate it by the psychological means.